Body Image and Macronutrient Intake as Predictors of Chronic Energy Deficiency in Adolescent Girls: A Cross-Sectional Study - Yustina Eno Bei; Astuti Nur; Asmulyati S Saleh (Media Publikasi Cendekia Indonesia, 2025)
Chronic Energy Deficiency (CED) is a serious nutritional problem to which adolescent girls are susceptible, and it can have detrimental effects on health and productivity. The prevalence of CED in Indonesia, particularly in Nusa Tenggara Timur (NTT), remains high. The factors causing CED are multifactorial, including direct factors such as macronutrient intake and indirect factors such as body image, which can trigger unhealthy dieting behaviors. This study aimed to analyze the relationship between body image and intake of energy, protein, fat, and carbohydrates with the incidence of CED in adolescent girls at SMAN 7 Kupang. This quantitative study employed a cross-sectional design and was conducted from February to June 2025 at SMAN 7 Kupang. A sample of 93 female students from grades X and XI was selected using the Simple Random Sampling technique. Body image data were collected using the MBSRQ-AS questionnaire, macronutrient intake using a 24-hour food recall form, and CED status was measured with a Mid-Upper Arm Circumference (MUAC) tape (cutoff <23.5 cm). Data analysis was performed using the chi-square test at a significance level of p<0.05. The majority of respondents were aged 15-16 years (66.7%) and came from families with income below the regional minimum wage (77.4%). Bivariate analysis results showed a significant relationship between negative body image (p=0.009), insufficient energy intake (p=0.016), insufficient protein intake (p=0.000), insufficient fat intake (p=0.024), and insufficient carbohydrate intake (p=0.030) with the incidence of CED.